Peningkatan Kedalaman Penetrasi Las Stainless Steel 304 dengan Medan Magnet Eksternal pada Pengelasan Autogenous Tungsten Inert Gas Welding - Haikal, Haikal; Chamim, Moch.; Andriyansyah, Deni; Wiyono, Apri; Baskoro, Ario Sunar; Isnarno, Isnarno (Jurnal Rekayasa Mesin, 2021)
In this study, research on the use of the External Magnetic Field method – Tungsten Inert Gas was done to determine the effect of welding arc compression on the quality of AISI 304 thin plate weld. The welding process was performed using autogenous welds. In this study, an external magnetic field was generated by placing a magnetic solenoid around the TIG welding torch. Enabling this electromagnetic field is done dynamically using a microcontroller. Welding parameters used are welding current 100; 105; 110 A and welding speed 1.6; 1.8; 2.05 mm/s. The results of this study showed that EMF-TIG welding can produce a more uniform bead width along the weld line with a standard deviation of 0.08 compared with conventional TIG welding of 0.12. Increased welding speed of 2.05 mm/s causes no effect on the addition of an external magnetic field to the width of the weld bead. The current parameters are 105 A with a speed of 1.6; 1.8; 2.05 mm/s resulted in compression of the top bead width by 0.87; 0.61; 0.1 mm. The welding parameters with a current of 105 A and welding speed of 1.6 mm/s have a larger upper bead compression effect of 0.84 mm compared to 110 A currents of 0.38 mm. Moreover, the D/W ratio obtained under an external magnetic field was higher than without magnetic.